Ash princess - Sebastian, Laura (New York : Delacorte Press, 2018)
Held captive by the brutal Kaiser since age six when she witnessed her mother's murder, Theodosia, called Ash Princess, is now sixteen and prepared to reclaim the throne by any means necessary.
Keywords: Princesses -- Fiction; Courts and courtiers -- Fiction; Kings, queens, rulers, etc. -- Fiction; Prisoners -- Fiction; Fantasy